Strategic Transformation of the Muhammadiyah Islamic Organisation through BPRS Matahari in Strengthening Sharia Financial Inclusion - Nugroho, Lucky; Putra, Yananto Mihadi; Doktoralina, Caturida Meiwanto; Purnama, Adhy (Social and Economic Bulletin, 2025)
The growth of Islamic banking in Indonesia has not been able to fully reach grassroots communities and MSME players, causing dissatisfaction, including from the Muhammadiyah community. The gap between the principle of justice and the reality of commercialization of Islamic institutions has created a need for new solutions. This study aims to examine the establishment of BPRS Matahari as Muhammadiyah's strategic repositioning in strengthening community-based Islamic financial inclusion. Furthermore, using descriptive qualitative methods through analysis of organizational documents, OJK regulations, academic literature, and online media, this study reveals the role of BPRS Matahari as a form of economic da'wah (proselytizing) as well as an intermediary instrument that favors the people. The results show that BPRS Matahari not only fills the void in Islamic financial services but also symbolizes the integration of theological, social, and economic values in accordance with the maqasid syariah. The support of the Muhammadiyah Social Enterprise (AUM) network creates a closed-loop ecosystem that strengthens the legitimacy and sustainability of the institution. These findings have theoretical implications by integrating the Tawhid String Relationship theory and institutional theory, as well as practical contributions to the development of a community-based Islamic microfinance model. The novelty of this research lies in its emphasis on the role of religious organizations as strategic actors in building inclusive, equitable, and sustainable institutional transformation.